Pengaruh Proses, People dan Physical Evidence Dalam Meningkatkan Kepuasan Mahasiswa di Universitas Baturaja: Pengaruh Proses, People dan Physical Evidence Dalam Meningkatkan Kepuasan Mahasiswa di Universitas Baturaja (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2021)
This research aims to analyze the effect of people, process amd phisical evidence On Colleger Satisfaction. Students College of Baturaja University were taken as the case studi. Both primary and secondary data were obtained in this study. Secondary data were obtained from various sources such as journals, books and other related publication. Primary data were obtained using questionnaires which were distributed to the target respondents. A Multiple Linear Regression Analysis with the SPSS v26 program was employed to analyze data. The result showed that people, process and physical evidence had a positive and significant effect on college satiffaction and process was found dominant. For further research, adding other variables such as product, price, and promotion was also suggested. It suggestted the referent group can help provide a better procedure and mechanisms for lectures activity and administrative service for colleger.